Play Therapy in Handling Child Trauma Victims of Domestic Violence (KDRT) - Amiyatuttazkiyah; Nina Fitriyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Child development determines the future of a nation. There are victims of violence that affect children, can recover therapeutically. Play therapy is an activity that uses games in a fun, safe and comfortable way as a therapeutic tool used by children to improve their behavior. The purpose of this study was to determine the effectiveness of play therapy in dealing with recovery from violence in the household. Therefore, I use this play therapy to victims of domestic violence on a child. In terms of existing problems, the method used in this study is to use library research to conduct research originating from the library in the form of books, encyclopedias, dictionaries, journals, theses, periodicals, and others.